The Role of Synthetic Biology in the Design of Microbial Cell Factories for Biofuel Production. - Verónica Leticia Colin; Rodríguez, Analía; Cristóbal, Héctor Antonio (Journal of Biomedicine & Biotechnology, 2011)
Insecurity in the supply of fossil fuels, volatile fuel prices, and major concerns regarding climate change have sparked renewed interest in the production of fuels from renewable resources. Because of this, the use of biodiesel has grown dramatically during the last few years and is expected to increase even further in the future. Biodiesel production through the use of microbial systems hasmarked a turning point in the field of biofuels since it is emerging as an attractive alternative to conventional technology. Recent progress in synthetic biology has accelerated the ability to analyze, construct, and/or redesign microbial metabolic pathways with unprecedented precision, in order to permit biofuel production that is amenable to industrial applications. The review presented here focuses specifically on the role of synthetic biology in the design ofmicrobial cell factories for efficient production of biodiesel.